Hysterectomy in patients with previous cesarean section: comparison between laparoscopic and vaginal approaches. (January 2015) - Bogani, Giorgio; Cromi, Antonella; Serati, Maurizio; Di Naro, Edoardo; Casarin, Jvan; Marconi, Nicola; Pinelli, Ciro; Ghezzi, Fabio
Abstract: Objective: To evaluate surgery-related outcomes of laparoscopic (LH) and vaginal hysterectomy (VH) in patients with a history of previous cesarean section (CS). Study design: Data on 289 consecutive patients with a history of CS undergoing VH ( n  = 49, 17%) and LH ( n  = 219, 76%) were collected. Basic descriptive statistics, univariate and multivariate analyses were performed to evaluate surgery-related outcomes. A propensity-matched algorithm was applied in order to reduce allocation biases between groups. Results: Patients undergoing LH were more likely to have a history of multiple cesarean sections (44% vs. 18%; p  = 0.001). Additionally, uterine weight was greater among patients undergoing LH than VH (median weight: 235 (range, 45–2830) vs. 150 (range, 40–710) g; p  < 0.001). Three patients in each group experienced procedural bladder injuries (3/219 (1%) vs. 3/49 (6%); p  = 0.07; RR: 1.65; 95%CI: 0.74, 3.68). The rate of grade 3 or worse postoperative complications was balanced between LH and VH (1% vs. 0%; p  = 1.00). Patients undergoing LH experienced a shorter length of hospital stay in comparison to patients undergoing VH (1 vs. 2 days; p  = 0.02). Considering the overall population, we observed via multivariate analysis that age (OR: 1.003 (95%CI: 1.001, 1.004) per 10-year increase in age; p  = 0.002), VH (OR: 17.80 (95%CI: 1.762, 180, 378); p  = 0.01) and number of cesarean sections ≥ 2 (OR: 27.70 (95%CI: 1.976, 388, 285); p  = 0.01) increased the risk of developing bladder injuries during hysterectomy. Conclusions: LH is a safe and feasible procedure in patients with previous CS, and it is associated with a low bladder injury rate.